2017
DOI: 10.1292/jvms.16-0188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum cystatin-C and symmetric dimethylarginine concentrations in dogs with heart failure from chronic mitral valvular insufficiency

Abstract: Reduction in glomerular filtration rate (GFR) is a common complication in advanced stages of heart failure (HF). The convenient and precise assessment for GFR would be useful for early detection of renal impairment in HF dogs. Our hypothesis of this study was the GFR would be reduced in advanced stages of HF from chronic mitral valvular insufficiency (CMVI), as indicated by renal markers including serum cystatin-C (Cys-C) and symmetric dimethylarginine (SDMA) concentrations. Forty-three client-owned dogs consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
(51 reference statements)
7
14
3
2
Order By: Relevance
“…It has been reported to be associated with inflammation and might play a role in myocardial fibrosis by interacting with transforming growth factor beta 35 . In mice, LRG1 has a protective function against adverse cardiac remodeling in experimentally induced myocardial infarction 53 . In our study, LRG1 was significantly increased in CHF cats.…”
Section: Discussionsupporting
confidence: 58%
“…It has been reported to be associated with inflammation and might play a role in myocardial fibrosis by interacting with transforming growth factor beta 35 . In mice, LRG1 has a protective function against adverse cardiac remodeling in experimentally induced myocardial infarction 53 . In our study, LRG1 was significantly increased in CHF cats.…”
Section: Discussionsupporting
confidence: 58%
“…There was close correlation of serum Cys-C and SDMA concentrations with serum creatinine, urea nitrogen, and the severity of HF. This study demonstrated that the GFR was decreased in dogs with CMVI having earlier stages of HF [28].…”
Section: Laboratory Testssupporting
confidence: 53%
“…The convenient and precise assessment for GFR would be useful for early detection of renal impairment in HF dogs. One recent study has evaluated the reduction in GFR in advanced stages of HF from CMVI, using renal markers including serum cystatin C (Cys-C) and symmetric dimethylarginine (SDMA) concentrations [28]. Forty-three clientowned dogs consisting of 33 dogs with different stages of HF from CMVI and 10 age-matched healthy dogs were enrolled in this study.…”
Section: Laboratory Testsmentioning
confidence: 99%
“…Nesse sentido, observou-se que a cistatina C detectou 78,6% (22/28) de cães com IRA enquanto a creatinina apontou apenas 28,5% (8/28) de ocorrência de IRA (Quadros 2 e 3). Esses dados indicam maior sensibilidade da cistatina C na identificação dos pacientes acometidos com IRA e estão em conformidade com estudos anteriores (Pasa et al 2008, Sasaki et al 2014, Shoukath & Patil 2014, Choi et al 2017) e que enfatizam a baixa sensibilidade da creatinina sérica no diagnóstico precoce de lesão renal (Braun et al 2003, Grauer 2005, Brown et al 2015. Devido a isto, alguns estudos sinalizam a necessidade de mudanças na utilização dos valores de referência da creatinina sérica e propõem o monitoramento longidutinal deste analito com a finalidade de classificar e estadiar os diferentes graus de lesão renal (Dalton 2011, Segev 2012, IRIS 2013.…”
Section: Discussionunclassified
“…A precocidade e a correlação entre a concentração sérica de cistatina C e TFG foram demonstradas anteriormente em cães com disfunção renal (Jensen et al 2001, Braun et al 2002, Wehner et al 2008, Miyagawa et al 2009, Pasa et al 2009, Didem et al 2015. Kavitha et al (2011) ao avaliarem cães com suspeita de lesão renal observaram aumento da cistatina C em 35%, e corroboraram sua superioridade comparada à creatinina, dados semelhantes foram encontrados por Choi et al (2017) ao avaliarem cães cardiopatas. Entretanto, estes estudos fizeram uma avaliação pontual deste biomarcador, não sendo realizado monitoramento longitudinal e em pacientes críticos.…”
Section: Discussionunclassified